2013
DOI: 10.1021/ol4010867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spirocarbamate Oxindoles via Intramolecular Trapping of a β-Silyl Carbocation by an N-Boc Group

Abstract: We report the Lewis acid catalyzed additions of allylsilanes to N-Boc-iminooxindoles and the formation of novel silicon-containing spirocarbamates via intramolecular trapping of a β-silyl carbocation by an N-Boc group. Several transformations display the synthetic utility of these spirocarbamate oxindoles, including a reductive cyclization to access new silylated furoindoline derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 63 publications
1
14
0
2
Order By: Relevance
“…The outcome of the allylation of isatin ketimines using allylsilanes is strongly affected by the nature of the catalyst employed to promote the addition reaction. The utilization of copper salts in the reaction of isatin ketimines with different trialkylallylsilanes 212 directly affords spirocarbamates 214 in satisfactory yield and generally moderate stereoselectivity (Scheme ) . Additives such as sodium tetrakis[(3,5‐trifluoromethyl)phenyl]borate 213 are instrumental in order to obtain better yields of the spiro derivatives, although it has been observed that this salt alone is not able to catalyze the reaction.…”
Section: Spiroheterocyclic Derivativesmentioning
confidence: 99%
“…The outcome of the allylation of isatin ketimines using allylsilanes is strongly affected by the nature of the catalyst employed to promote the addition reaction. The utilization of copper salts in the reaction of isatin ketimines with different trialkylallylsilanes 212 directly affords spirocarbamates 214 in satisfactory yield and generally moderate stereoselectivity (Scheme ) . Additives such as sodium tetrakis[(3,5‐trifluoromethyl)phenyl]borate 213 are instrumental in order to obtain better yields of the spiro derivatives, although it has been observed that this salt alone is not able to catalyze the reaction.…”
Section: Spiroheterocyclic Derivativesmentioning
confidence: 99%
“…The addition may lead to the formation of a β‐silyl‐stabilized carbocation, as perceived through classical silicon chemistry. Although elimination of the silyl group from the carbocation would give allylation product 1 in the classical cascade, it was observed that the cation was intercepted by the nucleophilic oxygen atom to give spirocyclic oxindole intermediate I . This intermediate was isolated, and the structure of its 5,7‐dimethyl analogue 2k was conclusively established by single‐crystal X‐ray analysis.…”
Section: Resultsmentioning
confidence: 99%
“…7; Table 3). Using the tert-butyl-substituted oxindole 1 f leads to trapping of the transient b-silyl carbocation and isolation of the lactone 8 f. [15,22] The yield of 8 f is influenced by the use of chloride versus triflate salt (53 versus 18 % yield, Table 3), which is attributed to Lewis acid initiated deprotection of the tertbutyl ester. The reaction of 1 f using excess NaBArF (60 mol %) promotes allylation with 95 % conversion (in 48 h).…”
Section: Methodsmentioning
confidence: 99%